Analisis Kemampuan Berhitung Siswa TK Setelah Melakukan Pembelajaran Berbasis Neurosains Dengan Pendekatan The Number Race - Lakshitani , Ignatia Dharmastuti; Lawalata, Daystera Jeskris (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
Neuroscience-based learning is learning that prioritizes the ability between interconnected neurons centered in the brain as a coordination of cognitive and affective thinking. Number Race is a mathematical intervention program that has six objectives, namely; strengthen number processing brain mechanism, build number line mentality, teach and practice counting, teach and practice initial addition and subtraction, encourage fluency, and help children with dyscalculia. Therefore, this study aims to analyze the numeracy skills of kindergarten students after conducting neuroscience-based learning with the Number Race approach. This research is a qualitative descriptive study. The results showed that more than 70% of students were able to perform basic calculations and 29% still made mistakes in solving the given questions. The results found are not 100% due to time constraints and a very short learning process. In addition, from a Neuroscience point of view, students’ numeracy skills are good because on average students are able to understand and perform addition operations with the learning media that have been made.